Answer to Question #20254 in Trigonometry for Kristen Woods
solve each quadratic in form equation
4. (x-2)^2-3(x-2)+2=0
1
2012-12-13T09:53:55-0500
& (x-2)^2-3(x-2)+2=0
Let's find the discriminant of the given equation:
D = (-3)² - 4*1*2 = 9 - 8 = 1.
Now we can use the formula for the roots of a quadratic equation:
x-2 = ( -(-3) ± √D ) / (2*1) = ( 3 ± 1 ) / 2 = {2, 1}.
Therefore,
x1 - 2 = 2 ==> z1 = 4
and
x2 - 2 = 1 ==> x2 = 3.
So, this equation has two different solutions: {4, 3}.
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment